Perioperative Anesthetic Management in Repair Diaphragmatic Hernia with Atrial Septal Defect and Pulmonary Hypertension - Noorrahman, M Irvan; Ananda, Pratama; Anggraeni, Novita (Faculty of Medicine-Universitas Airlangga, 2024)
Introduction: Patients who had suffered disease of atrial septal defect (ASD) coming by pulmonary hypertension (PH) often present a clinical dilemma. Both of these disorders are congenital anomalies that often appear in pediatrics. Anaesthetic management in diaphragmatic hernia repair with this comorbidity requires precision and accuracy to avoid morbidity and mortality during surgery. The right management and care of anesthetic procedures is needed for patients who will be operated on with these two disorders. Objective: To describe the anesthetic management of a diaphragmatic hernia repair patient with comorbid ASD and pulmonary hypertension. Case report: The patient, a 1.5-month-old female baby born, has presented with shortness of breath complaints since the birth. Those were born spontaneously at the midwife's office and did not cry immediately, and a history of blueing and decreased consciousness was admitted for 20 days. Based on the examination, the diagnosis of diaphragmatic hernia from echocardiography found ASD and PH with a left ventricular ejection fraction of 64%. The patient was planned for diaphragmatic hernia repair under general anesthesia. Induction of anesthesia was performed with 5 mcg of fentanyl and inhalation anesthetic 3.5 vol% sevoflurane. After the endotracheal tube (ETT) was attached, the patient was desaturated to 50%, then the hyperventilated oxygenation was performed and positioned with knee chest position, and then milrinone at a dose of 1 mcg/min was given, saturation rose to 100%. During intraoperative ventilation control with manual bagging and maintenance anesthesia with inhalation ansethetic sevoflurane of 3.2 vol%. After surgery, the patient was admitted and observed in the pediatric intensive care unit for 2 days before extubation. Conclusion: Appropriate perioperative management in ASD patients with PH can reduce perioperative morbidity and mortality.